Способ ускорения электронов в цилиндрическом бетатроне и устройство для его реализации - Касьянов В. А. Валерий Алексеевич; Москалев В. А. Владилен Александрович; Цимбалист А. В.; Шестаков В. Г.
опубл. 27.12.1996